Modern marketing strategy at US airports - Rankin, William (Henry Stewart Talks, 2009)
Decision-making in marketing, Strategic marketing plan factors, Management objectives and questions, Waco Regional Airport case study: goals, strengths, weaknesses, opportunities, strategy considerations
Archived at 2022/04/04